answer with explanation plz
Attachments:
![](https://hi-static.z-dn.net/files/dd9/e45d04596c5fb9d1f5df833e3ee192e2.jpg)
Answers
Answered by
1
Answer:
Answer:
-a⁸ + b⁸ = (b⁴ + a⁴)(b² + a²)(b + a)(b - a)
Step-by-step explanation:
Factorise :- a 8 + b 8
-a⁸ + b⁸
= b⁸ - a⁸
= (b⁴)² - (a⁴)²
Using x² - y² = ( x+ y)(x -y)
here x = b⁴ & y = a⁴
= (b⁴ + a⁴)(b⁴ - a⁴)
= (b⁴ + a⁴)( (b²)² - (a²)²)
= (b⁴ + a⁴)(b² + a²)(b² - a²)
= (b⁴ + a⁴)(b² + a²)(b + a)(b - a)
-a⁸ + b⁸ =
Similar questions
Math,
2 months ago
Environmental Sciences,
2 months ago
English,
2 months ago
Math,
4 months ago
Computer Science,
11 months ago
English,
11 months ago